Instagram As A Platform For Personal Branding - Sari Endah Nursyamsi; Nasaruddin Siregar; Arief Yanto Rukmana; Wandi Kurniadi; Geofakta Razali (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
One of the communication strategies that implants a positive perception of a person in the public is personal branding. The presence of Instagram has a function, which is to create a social media marketing strategy and build a brand. With the presence of Instagram, it can influence the behaviour of its followers. One of them is the Instgarm Akbar Maulana selebgram, known as the famous Personal Ajudan because his personality is considered pleasant and entertaining. This research method is qualitative descriptive, with a focus on the case study of the research, which is to find out the form of personal branding Akbar Maulana uses through his social media account Instagram. Supported by Peter Montoya’s eight core personal branding concepts, his research shows that Akbar Maulana’s personal branding meets eight key concepts: specialisation, leadership, personality, difference, appearance, unity, firmness and good name. With a distinctive and strong character in shaping personal branding as a smart, vigorous, and entertaining teenager. Not only that, using the Instagram app that has supplemented a variety of special features with various decorations when making videos, then uploading them to the Instagram media account